Climate Change and Diet - Neha Bose; Thomas Hills; Daniel Sgroi (Institute of Labor Economics (IZA), 2020)
Though many in the general public are concerned about climate change, most are unaware that agriculture and food production accounts for about one quarter of aggregate green house emissions and therefore, diet change is one of the most effective ways that individuals can reduce their climate impact. To investigate how best to communicate this, we present the results of a pre-registered randomised control trial, involving 1220 subjects, exploring six different information interventions. Our findings indicate that the most influential interventions are based on scientific knowledge and efficacy salience. These effects are mediated by prior beliefs and individual characteristics. Providing information on the health impact of a plant-based diet was most effective for individuals with pre-existing health concerns. The greatest resistance to this information was associated with motivated reasoning around meat consumption: the more meat a participant consumed the less they reported knowing about the relationship between diet and climate before the study, the more resistant they were to new information demonstrating that relationship, the lower their efficacy beliefs around climate change, and the more likely they were to take moral offence at being informed. Our results suggest that while many people are open to dietary change and are responsive to scientific evidence, the largest potential for impact between diet and climate may be in overcoming pre-existing biases associated with sacred values around meat consumption.
Keywords: Q54; D91; I12; C90; 330; self efficacy; decit model of science communication; nudge; interventions; environment; agriculture; vegan; vegetarian; diet; climate change; motivated reasoning; cognitive dissonance; strategic ignorance; social norms